Tobacco smoking patterns in the emirate of Abu Dhabi, United Arab Emirates: a comprehensive analysis of trends before and after the onset of the COVID-19 pandemic - Alam, Zufishan; Elbarazi, Iffat; Al Shehhi, Budoor; AlSafi, Maha Mohamed; Al Wahedi, Mariam; Maarouf, Ilfat Assaad; Hassan, Aamir; Al-Houqani, Mohammed (Frontiers in Public Health, 2025)
IntroductionTobacco smoking is a leading yet preventable risk factor for morbidity and mortality worldwide. As in western countries, the Arab world also encounters the growing tobacco epidemic. Assessment of smoking prevalence is a key step in identification of emerging trends, thus enabling planning of preventive measures.MethodsThis study aimed to evaluate the prevalence of tobacco smoking among applicants of the Premarital Screening Program, in Abu Dhabi, United Arab Emirates during 2019–2023. Data was collected from all participants who applied for the program, through a questionnaire enquiring about tobacco smoking habits and methods of use. Overall smoking prevalence was assessed for the five-year period, as well as individually for each year. Smoking patterns were observed for three distinct COVID-19 periods: pre-COVID (2019), peri-COVID (2020–21) and post-COVID (2022–23). The smoking patterns were also examined by gender and nationality status. The findings are based on responses of 74791 applicants, of which 47% were females and 68.4% UAE nationals.ResultsThe reported overall tobacco smoking prevalence was 14.6%, with cigarette and Midwakh (handheld pipe) being the most commonly used methods (6.6%), followed by water pipe (2.2%). Smoking levels were reported to be significantly higher in men and UAE nationals compared to women and non-nationals respectively. A general decline was observed in point prevalence of tobacco smoking levels from the pre-COVID period (19.1%) to the peri-COVID period (15.1%), and further to the post-COVID period (13.5%) as the pandemic restrictions eased.DiscussionThere is a need of control measures and interventions to maintain the positive behavioral change, brought by the COVID-19 that resulted in tobacco use reduction. Furthermore, steps to curb use of Midwakh, which is becoming an increasingly popular method of choice, are also required.